Effect of helium flux on near-surface helium accumulation in plasma-exposed tungsten. (5th November 2021) - Nandipati, Giridhar; Hammond, Karl D; Maroudas, Dimitrios; Roche, Kenneth J; Kurtz, Richard J; Wirth, Brian D; Setyawan, Wahyu
Abstract: We report results of object kinetic Monte Carlo (OKMC) simulations to understand the effect of helium flux on the near-surface helium accumulation in plasma-facing tungsten, which is initially pristine, defect-free, and has a (100) surface orientation. These OKMC simulations are performed at 933 K for fluxes ranging from 10 22 to 4 × 10 25 He/m 2  s with 100 eV helium atoms impinging on a (100) surface up to a maximum fluence of 4 × 10 19 He/m 2 . In the near-surface region, helium clusters interact elastically with the free surface. The interaction is attractive and results in the drift of mobile helium clusters towards the surface as well as increased trap mutation rates. The associated kinetics and energetics of the above-mentioned processes obtained from molecular dynamics simulations are also considered. The OKMC simulations indicate that in pristine tungsten, as the flux decreases, the retention of implanted helium decreases, and its depth distribution shifts to deeper below the surface. Furthermore, the fraction of retained helium diffusing into the bulk increases as well, so much so that for the flux of 10 22 He/m 2  s, almost all of the retained helium diffused into the bulk with minimal/negligible near-surface helium accumulation. At a given flux, with increasing fluence, the fraction of retained helium initially decreases and then starts to increase after reaching a minimum. The occurrence of the retention minimum shifts to higher fluences as the flux decreases. Although the near-surface helium accumulation spreads deeper into the material with decreasing flux and increasing fluence, the spread appears to saturate at depths between 80 and 100 nm. We present a detailed analysis of the influence of helium flux on the size and depth distribution of total helium and helium bubbles.